Motivasi dan Minat Belajar Matematika Siswa Madrasah Tsanawiyah Dan Pengaruhnya terhadap Hasil Belajar Matematika - Yolanda, Firly Adizah; Mismar, Sari Novia; Idris, Khairiani (Delta: Jurnal Ilmiah Pendidikan Matematika, 2024)
Motivation and interest in learning mathematics have been acknowledged as among factors affecting mathematics learning outcomes. This is a quantitative study aims to investigate the effect of mathematics learning motivation and interest on mathematics learning outcomes of students. Study population was all of students of MTsN 2 Lhoksemawe, Aceh Province, while study samples involved 30 students from Class VII. Study data involved scores of mathematics learning motivation and mathematics learning interests which were collected by using quistionnaires, while mathematics learning outcomes were measured by using mathematics scores on students’ semester report cards. Data was analyzed statistically using descriptive, correlation, and regression analyses. Results showed that: (1) students’ mathematics learning motivation and interest were in the sufficient category, with motivation mean score was 72.24% and interest mean score was 70.45%; (2) mathematics learning motivation and mathematics learning interest were significantly and positively correlated with mathematics learning outcomes in the moderate category; (3) The effect of learning motivation (X1) and learning interest (X2) on learing outcomes (Y) was presented by regression model Y=78,287+0,066X1+0,037X2. The model could explain 22% of variations within the learning outcomes variable, while the reminder of 78% could be affected by other variables outside the model.